Long-term outcomes of endoscopic submucosal dissection and comparison to surgery for superficial esophageal squamous cancer: a systematic review and meta-analysis. (November 2020) - Yeh, Jen-Hao; Huang, Ru-Yi; Lee, Ching-Tai; Lin, Chih-Wen; Hsu, Ming-Hung; Wu, Tsung-Chin; Hsiao, Po-Jen; Wang, Wen-Lun
Aim: The aim of this study was to investigate the long-term outcomes of endoscopic submucosal dissection (ESD) for superficial esophageal squamous cancer. Methods: A literature search was conducted using PubMed, ProQuest and Cochrane Library databases. Primary outcomes were overall survival, disease-specific survival and recurrence-free survival at 5 years. Secondary outcomes included adverse events, recurrence and metastasis. Hazard ratios were calculated based on time to events for survival analysis, and odds radios were used to compare discrete variables. Results: A total of 3796 patients in 21 retrospective studies, including 5 comparative studies for ESD and esophagectomy were enrolled. The invasion depth was 52.0% for M1–M2, 43.2% for M3–SM1 and 4.7% for SM2 or deeper. The 5-year survival rate was: overall survival 87.3%, disease-specific survival 97.7%, and recurrence-free survival 85.1%, respectively. Pooled local recurrence of ESD was 1.8% and metastasis was 3.3%. In terms of the comparison between ESD and esophagectomy, there was no difference in the overall survival (86.4% versus 81.8%, hazard ratio = 0.66, 95% CI = 0.39–1.11) as well as disease-specific and recurrence-free survival. In addition, ESD was associated with fewer adverse events (19.8 % versus 44.0%, odds ratio = 0.3, 95% CI = 0.23–0.39). Conclusions: For superficial esophageal squamous cancer, ESD may be considered as the primary treatment of for mucosal lesions, and additional treatment should be available for submucosal invasive cancers.